Implications of Belt and Road Initiative for supply chain management: A holistic view - Atif Saleem Butt; Tahseen Anwer Arshi; Venkoba Rao; Veena Tewari (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Belt and Road Initiative (BRI), one of the largest logistics and transportation infrastructures to date, has focused on much work in the economics and political sciences. However, little research has been done on how BRI can affect supply chain management on the whole. Since BRI is a large-scale logistics infrastructure-building project, it is clear that it will have several implications for supply chains. This study aimed to fill this gap in supply chain management literature within the context of the BRI. In particular, this paper aimed to unveil the potential challenges and threats that BRI may bring to supply chain management. Using 20 semistructured interviews with supply chain managers located on the BRI lane in South Asian countries (Pakistan, India, Bangladesh, etc.), this study posed six distinct implications of BRI for logistics and supply chain management. This article concludes by articulating its contributions to theory and practice and, finally, limitations and future research directions.
Keywords: 650; Belt and Road Initiative; logistics management; supply chain management; transportation